Load control and management of distribution network with renewables under power market - Mohammad Arif Bin Rashidi @ Tham Wei Ming (Nanyang Technological University, 2023)
With the increase in demand for more power, it is crucial to be conscious of the finite nature of fossil fuels as our main source of energy. Therefore, it would be beneficial to consider a more sustainable means of generating renewable energy. As a country with limited land space, solar photovoltaics (PV) is an excellent alternative source of power generation. PV systems are integrated into the current grid, enabling us to generate cleaner energy and reduce carbon emissions, which may represent the future of widespread energy storage technology (ESS). Potentially, we may be able to install Direct Current (DC) technology in parallel with our current Alternating Current (AC) system, which can be connected to our PowerGrid (PG) low-voltage (LV) system, which provides electricity for much of our residential and commercial buildings. Therefore, it presents an opportunity to explore options, integrating load control and management technology such as an energy storage system (ESS) in the existing PV system, which would create an efficient PowerGrid (PG) system that allows for cleaner, affordable, and reliable energy for our future. Through this project, we intend to examine how the distribution network has changed and how the integration of renewables technologies such as PV and ESS systems can improve load control and management of energy for the distribution network to utilize existing or ongoing solar installations, which could reduce energy course that would potentially reduce our electricity tariff.